Kehidupan Islami dan Pemanfaatan Teknologi Digital sebagai Strategi Pendidikan Berkemajuan Muhammadiyah - Samsiyah Nuril Hidayah; Yolanda Dwintarisma Andrini; Eka Sri Rusminingsih; Heri Rifhan Halili (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to analyze the role of Islamic life in Muhammadiyah education, examine the utilization of digital technology in the learning process, and formulate strategies for integrating Islamic values and digital technology within the framework of Muhammadiyah’s progressive education in the digital era. This research employs a qualitative approach through a library research design with a descriptive-analytical method. Data were collected from relevant scholarly sources, including academic books, peer-reviewed journal articles, official Muhammadiyah documents, and educational policy reports, and were analyzed using qualitative thematic analysis through stages of data reduction, thematic classification, conceptual synthesis, and conclusion drawing. The findings indicate that Islamic life plays a central role as a normative and ethical foundation in Muhammadiyah education through the internalization of Islamic values in learning activities, religious habituation, and structured social engagement, which contribute to the strengthening of students’ religious character, discipline, and social awareness. In addition, the use of digital technology through e-learning platforms, educational applications, and interactive learning media has been shown to enhance learning effectiveness, quality, and student participation. The integration of Islamic life and digital technology within the curriculum of Muhammadiyah’s progressive education creates a balanced development of academic competence, digital literacy, and Islamic character formation, despite challenges related to infrastructure limitations, teachers’ digital competencies, and the potential misuse of technology. This study concludes that the systematic integration of Islamic values and digital technology represents a relevant and effective strategy for improving the quality of Muhammadiyah education in the digital era.